ANALISIS KOMITMEN DARI TOKOH UTAMA DALAM DRAMA THE MERCHANT OF VENICE KARYA WILLIAM SHAKESPEARE - FATGEHIPON, NOVITASARI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT The Merchant of Venice is a drama written by William Shakespeare. It is a popular comedy drama that was published in 1596. William Shakespeare shows how important a commitment in human life as shown in this drama. In addition, this drama makes us understand about how to show our commitment to someone or ourself. Therefore, commitment becomes the topic of this research. The problem of this research is how the main characters’ commitment is depicted in the drama The Merchant of Venice. The objective of this research is to identify, analyze and describe the main characters’ commitment shown in this drama. In analysing this research, the writer used Robert’s theory, Mc Crimmon’s theory and several concepts about Commitment The results indicate that there are two kinds of commitment shown by the main characters namely positive commitment and negative commitment. The examples of positive commitment found in this drama are sacrifice, loyalty, consistency, and generousity. Whilst, the negative commitment is shown through the character’s plan to murder. Keywords: Drama, The Merchant of Venice, Commitment, Characters